Cobalt bullets or cobalt-fortified soybean oil meal for heifers on a finishing ration - Koch, R.A.; Smith, E.F.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Twenty-seven head of Hereford heifers of good to choice quality were used in this trial. They previously had been used to study various winter treatments. Treatments were as follows: control lot. Cracked sorghum grain and alfalfa hay fed twice a day; soybean oil meal fed once a day. Cobalt-bullet lot. Each heifer given a cobalt bullet at beginning of the feeding period; fed the same as the control lot. Cobalt “fed” lot. Daily allowance of supplemental cobalt carried in soybean oil meal; fed the same as the control lot. During the first 17 days of the trial, each heifer received 10 pounds of silage per day mixed with the grain to help brig to full feed. Heifers in the cobalt “fed” lot received 0.75 mg. of supplemental cobalt per head per day in their soybean oil meal during the first 90 days. During the last 80 days, the supplemental cobalt was increased to 1.50 mgs. per head per day.
Keywords: Beef; Cobalt; Soybean oil; Heifers